2022
DOI: 10.1038/s41467-022-30353-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation and zinc-induced transition modulate synaptic distribution and association of autism-linked CTTNBP2 and SHANK3

Abstract: Many synaptic proteins form biological condensates via liquid-liquid phase separation (LLPS). Synaptopathy, a key feature of autism spectrum disorders (ASD), is likely relevant to the impaired phase separation and/or transition of ASD-linked synaptic proteins. Here, we report that LLPS and zinc-induced liquid-to-gel phase transition regulate the synaptic distribution and protein-protein interaction of cortactin-binding protein 2 (CTTNBP2), an ASD-linked protein. CTTNBP2 forms self-assembled condensates through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 68 publications
2
28
0
Order By: Relevance
“…DRACC1 has an intrinsically disordered domain (IDR) in its C-terminal end similarly to other proteins that undergo LLPS, such as TDP-43, FMRP, and CTTNBP2 (Shih et al, 2022; Tsang et al, 2019; Zbinden et al, 2020). Dynamics of DRACC1 in neurons observed by time-lapse imaging look similar to that of TLS/FUS (Fujii et al, 2005), which is among the first identified and best characterized RNA-binding proteins in the field of phase separation (Zbinden et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…DRACC1 has an intrinsically disordered domain (IDR) in its C-terminal end similarly to other proteins that undergo LLPS, such as TDP-43, FMRP, and CTTNBP2 (Shih et al, 2022; Tsang et al, 2019; Zbinden et al, 2020). Dynamics of DRACC1 in neurons observed by time-lapse imaging look similar to that of TLS/FUS (Fujii et al, 2005), which is among the first identified and best characterized RNA-binding proteins in the field of phase separation (Zbinden et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study by Tseng et al showed that the human SLC39A8-p.391T missense variant (corresponds to the risk allele of rs13107325) reduced zinc transport (into the cell) in cell models [71], which was consistent with our observations in this study (i.e., zinc concentration was dysregulated in SLC39A8-p.391T knock-in mice compared with wild-types). Zn 2+ has a critical role in the brain, including regulating synaptic plasticity through microtubule stability [72], CTTNBP2 condensates [73], and BDNF signaling Consistent with its important roles in the Zinc concentration has been reported to be associated with several neuropsychiatric disorders [75], including schizophrenia [76,77] and Alzheimer's disease [78]. Zn 2+ is mainly distributed in the central nervous system (CNS) and stored in synaptic vesicles at several glutamatergic nerve terminals, and released upon its neuronal activity [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…ASD-related mutations in cortactin-binding protein 2 alter its condensation and synaptic distribution, leading to social impairment in mice. 68 Rett syndrome is a progressive X-linked neurodevelopmental disorder characterized by severe mental disabilities and autism-like symptoms, mainly caused by loss-of-function mutations in MeCP2. 75 Previous studies have demonstrated that loss or doubling of MeCP2 leads to postnatal neurodevelopment disorders.…”
Section: Phase Separation In Neurodevelopmental Disordersmentioning
confidence: 99%
“…Cortactin‐binding protein 2, an ASD‐linked protein, forms phase‐separated condensates via its C‐terminal IDR and promotes SHANK3 cocondensation in dendritic spines. ASD‐related mutations in cortactin‐binding protein 2 alter its condensation and synaptic distribution, leading to social impairment in mice 68 . Rett syndrome is a progressive X‐linked neurodevelopmental disorder characterized by severe mental disabilities and autism‐like symptoms, mainly caused by loss‐of‐function mutations in MeCP2 75 .…”
Section: Phase Separation In Synaptopathiesmentioning
confidence: 99%